Soil nutrient dynamics relate to Epichloë endophyte mutualism and nitrogen turnover in a low nitrogen environment. (November 2022) - Chen, Zhenjiang; White, James F.; Malik, Kamran; Chen, Hao; Jin, Yuanyuan; Yao, Xiang; Wei, Xuekai; Li, Chunjie; Nan, Zhibiao
Abstract: Colonization by foliar fungal endophytes can assist host plants in the acquisition of soil nutrients, however understanding of the effects of Epichloë endophytes on soil nutrient dynamics and their consequences for nitrogen cycling remains fragmentary. Here, we studied the microbial functional genes involved in the soil nitrogen cycle and soil nutrient dynamics along a nitrogen gradient in rhizosphere soil of ryegrass infected by the endophyte Epichloë festucae var . lolii . High-throughput sequencing was used to determine the community of microbial functional genes. Plant nutrients and soil N2 O flux were measured. The endophyte presence reduced the plant nutrient traits (shoot organic carbon, total nitrogen and total phosphorus, and root total phosphorus) under low nitrogen, while it increased the soil nutrient accumulation and altered the microbial environment. Plants with fungal endophyte showed higher community diversity in the AOB -amoA gene (ammonia-oxidation bacteria), had lower absolute and relative abundances in the nirK gene (nitrite reduction bacteria), and improved relative abundances and community diversity of the nosZ ( nitrous oxide reduction bacteria). The nifH gene (N2 fixing bacteria) showed higher absolute and relative abundances, and diversity in rhizosphere soil of endophyte-infected plants. Changes in plant and soil traits mediated by endophyte infection were closely related to N2 O fluxes and nifH gene abundance. The changes in CO2 flux by changing in soil microbial biomass nitrogen mediated by shoot biomass (induced by endophyte infection), which further altered the soil pH and NO3 − content and lead to an increased in NH4 + accumulation. The current study demonstrated that the possible mechanism for endophyte-mediated nutrient uptake might promote the NH4 + accumulation through nitrogen mineralization and NO3 − isomerization rather than enhancing in the nitrogen fixation process and inhibiting the denitrification process in N limited samples. By underlining the importance of endophyte infection for nutrient accumulation in plant and soil and biomass, these findings suggested that nutrient availability could initiate endophyte infection effects to mitigate the damage of low N stress for the host. Highlights: Nutrient availability mitigates low N stress by initiating endophyte effects. Increased in soil microbial biomass carbon and nitrogen by endophyte infection. Endophyte-infected plant reduced nitrous oxide (N2 O) flux and increased CO2 flux. Endophyte-mediated nutrient uptake associated with soil NO3 − dissimilation.